Normalization Bernstein Basis For Solving Fractional Fredholm-Integro Differential Equation - Al-Jubory, Abdul Khaleq O.; Salih, Shaymaa Hussain (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this work, we employ a new normalization Bernstein basis for solving linear Freadholm of fractional integro-differential equations  nonhomogeneous  of the second type (LFFIDEs). We adopt Petrov-Galerkian method (PGM) to approximate solution of the (LFFIDEs) via normalization Bernstein basis that yields linear system. Some examples are given and their results are shown in tables and figures, the Petrov-Galerkian method (PGM) is very effective and convenient and overcome the difficulty of traditional methods. We solve this problem (LFFIDEs) by the assistance of Matlab10.